The Effect of Self-Control on Continual Binge-watching of Netflix Movies and Youtube Videos by Young Adults in the Post-pandemic Period - Andrya, Amanda Putri; Imawati, Rochimah; Rahmawati, Yuliana Mukti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Binge-watching is a behavior that is often carried out by many people, especially when the COVID-19 pandemic hit with limited activities; individuals are also looking for other alternatives, one of which is watching. Along with the increase in Video-On-Demand on streaming applications, Netflix and YouTube make it easier for users to watch wherever and whenever. Unfortunately, this pandemic habit affects the way individuals organize and control themselves in the post-pandemic period, especially in early adulthood, because they are the generation that has easy access to watching using various media technologies. The method used in this research is quantitative, with a non-probability sampling technique using voluntary sampling. The analysis used is simple regression analysis to determine the effect of the independent variables on the dependent variable. This study (N = 270) shows an influence between binge-watching and self-control, with 17.7% motivated by seeking pleasure, filling free time, spending time together, adding insight, and escaping reality. Conversely, this behavior also causes procrastination, sleep disturbance, constant desire to eat, and addiction to watching movies.